Prevalence of mastitis and its associated risk factors in lactating camels in Northern Egypt - Abdelfattah Selim; Mohamed Marzok; Hattan S. Gattan; Hesham Ismail (PLoS ONE, 2025)
Dromedary camels are susceptible to mastitis, a multifactorial disease affecting dairy animals worldwide and leading to significant economic losses, particularly due to its subclinical form. However, limited data exist on the prevalence and risk factors associated with lactating camel mastitis in Egypt. Therefore, a cross-sectional study was conducted across three Egyptian governorates to assess the prevalence and identify potential risk factors. A total of 390 lactating camels were examined for both clinical and subclinical mastitis using the California Mastitis Test (CMT). The overall prevalence of mastitis was 38.46% (150/390), comprising 6.4% (25/390) clinical and 32.1% (125/390) subclinical cases. Significant associations (p < 0.05) were observed between mastitis prevalence and factors such as age, lactation stage, tick infestation, milking hygiene, and the presence of udder or teat lesions. The likelihood of mastitis was six times higher in camels older than five years, three times higher during early lactation, twice as high in the presence of tick infestation, twice as high with poor milking hygiene, and three times higher in animals with udder or teat lesions. Among the 600 quarter milk samples obtained from positive animals, mastitis-causing pathogens were isolated from 380 samples (63.3%), while 220 samples (36.7%) showed no bacterial growth. Streptococcus spp. (excluding S. agalactiae) and Escherichia coli were the most prevalent isolates (26.1% and 25%, respectively), whereas S. agalactiae was the least frequent, detected in only 5.5% of the samples. These findings highlight the importance of implementing integrated control measures to reduce mastitis prevalence, enhance camel milk quality, mitigate economic losses, and safeguard public health.